Ambiguity in Translation of Metaphors: A Case of Dholuo and Kiswahili - Oluoch , J. Stephen; Ipara , I. O.; M. , J. (African Journal of Education,Science and Technology (AJEST), 2014)
This study investigates ambiguity in the translation of Christian religious metaphors from Dholuo into Kiswahili through a pragmatic approach. Data is drawn from the sermons delivered in Dholuo and translated into Kiswahili. Sampled texts are analyzed and classified in a category referred to as ambiguity. The findings show various causes of ambiguity, mainly, socio-cultural differences and wrong inferences. This can be generalized to apply to translation problems associated with similar contexts. The article gives insight and suggestions in the application of pragmatic theories of communication in translation.